2019
DOI: 10.1002/hbm.24752
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the brain: Perceived stress mediates the impact of the superior frontal gyrus spontaneous activity on depressive symptoms in late adolescence

Abstract: Identifying factors for the prediction of depression is a long‐standing research topic in psychiatry and psychology. Perceived stress, which reflects the tendency to appraise one's life situations as stressful and overwhelming, has emerged as a stable predictor for depressive symptoms. However, the neurobiological bases of perceived stress and how perceived stress influences depressive symptoms in the healthy brain remain largely unknown. Here, we investigated these issues in 217 healthy adolescents by estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 123 publications
(225 reference statements)
2
53
0
Order By: Relevance
“…Two hundred thirty‐four local high school students aged 16 to 20 years (112 males, mean age = 18.6 years, SD = 0.78) participated in the study, all of whom were right‐handed native Mandarin Chinese speakers and were recruited from an ongoing neuroimaging project with the purpose of exploring the behavioral and neural substrates underlying social abilities, personality, and academic achievement among adolescents in Chengdu, China (Li et al, ; Wang et al, , ; Wang, Dai, et al, ; Wang, Zhao, et al, ). All participants were healthy and had no history of psychiatric or neurological diseases according to their records in the student archives from the schools and their self‐reports for two items (i.e., “Have you and your parents ever had any neurological illnesses?” and “Have you and your parents ever had any psychiatric illnesses?”) (Wang et al, ). Three participants were excluded from the following analyses as a result of abnormal brain morphological structure (e.g., unusual cysts).…”
Section: Methodsmentioning
confidence: 99%
“…Two hundred thirty‐four local high school students aged 16 to 20 years (112 males, mean age = 18.6 years, SD = 0.78) participated in the study, all of whom were right‐handed native Mandarin Chinese speakers and were recruited from an ongoing neuroimaging project with the purpose of exploring the behavioral and neural substrates underlying social abilities, personality, and academic achievement among adolescents in Chengdu, China (Li et al, ; Wang et al, , ; Wang, Dai, et al, ; Wang, Zhao, et al, ). All participants were healthy and had no history of psychiatric or neurological diseases according to their records in the student archives from the schools and their self‐reports for two items (i.e., “Have you and your parents ever had any neurological illnesses?” and “Have you and your parents ever had any psychiatric illnesses?”) (Wang et al, ). Three participants were excluded from the following analyses as a result of abnormal brain morphological structure (e.g., unusual cysts).…”
Section: Methodsmentioning
confidence: 99%
“…The SFG is thought to be involved in cognitive functions and emotion regulation-related processes, such as working memory and depression (Niendam et al, 2012), and low-frequency oscillation stimulation of the left SFG enhances working memory (Frank et al, 2014;Alagapan et al, 2019). It has been reported that perceived stress was positively correlated with fALFF in the left SFG and MFG, which play a partial mediating role in the relationship between perceived stress and depression (Wang et al, 2019). The DCG, PCG, and the precuneus are critical parts of the default mode network (DMN), which is related to cognition and emotion (Cavanna and Trimble, 2006;Leech and Sharp, 2014;Caruana et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, researchers have become increasingly interested in adolescent stress as a transdiagnostic risk factor because of its prevalence and its association with internalizing and externalizing disorders [23][24][25] as well as a host of other negative consequences, including poorer physical and academic outcomes. Adolescence is also a developmental stage where individuals may be particularly sensitive to stress due to shifts in hypothalamic-pituitary-adrenal axis reactivity, leading to more intense hormonal responses to stressors, particularly in older adolescents [26].…”
Section: Stress As a Risk Factor In Adolescencementioning
confidence: 99%